Biblioshiny-Based Knowledge Mapping of Entrepreneurship and SMEs in Innovation Ecosystems - Aulia utami putri; Ermanovida Ermanovida; Rizka Azzahri; Trecy Austin; Abubaccar Baldeh (Universitas Islam Negeri (UIN) Salatiga, 2025)
This study aims to map the intellectual landscape of research on entrepreneurship and small and medium-sized enterprises (SMEs) within multi-stakeholder innovation ecosystems using a bibliometric approach through Biblioshiny. A total of 38 Scopus-indexed articles published between 2010 and 2025 were analyzed to identify publication trends, thematic structures, conceptual evolution, and collaborative research patterns. The findings reveal a significant increase in scholarly attention to the topic, particularly after 2020, driven by the growing relevance of collaborative innovation, digital transformation, and ecosystem-based approaches to SME development. Key themes emerging from the knowledge mapping include entrepreneurial ecosystems, open innovation, sustainability, SMEs’ innovation capabilities, and multi-actor collaboration involving government, academia, industry, and community. The study highlights Brazil, Spain, the United Kingdom, and Australia as major contributors, with notable participation from emerging economies such as Indonesia. Three-field plots, thematic maps, and co-occurrence networks indicate that current research increasingly integrates theoretical foundations of innovation systems with contemporary issues such as digitalization and green entrepreneurship. This study contributes to the literature by offering a comprehensive overview of global research patterns and identifying thematic gaps that provide strategic directions for future studies on ecosystem-based SME development.